Assessing the effect of some plant extracts on Fusarium oxysporum f.sp. cubense - Tebeila, Mashego Kabelo (Vaal University of Technology, 2022)
Fusarium oxysporum f.sp.. cubense (FOC) causes fusarium wilt, one of the most destructive diseases of bananas. The management of F. oxysporum through synthetic fungicides causes serious environmental problems and threatens to non-target organisms. Medicinal plants may be a good substitute for synthetic fungicides due to their fewer negative impacts on human and ecological health. This study assessed the antifungal effect of crude extracts of Allium cepa L, Allium sativum L, Curcuma longa L, Tulbaghia violacea Harv, and Zingiber officinale L against FOC. The extracts were prepared using acetone, methanol, and water through maceration. Qualitative phytochemical screening was performed using standard methods. The plant extracts’ total phenolic and tannin content was determined using the Folin Ciocalteu method. Total flavonoids were determined by using the aluminium chloride colourimetric method. The antifungal activity of the extracts was determined by well diffusion, microtiter, and poisoned food techniques. High-Performance Liquid Chromatography (HPLC) profiling of standard phenolic compounds in T. violacea and A. sativum was conducted. Most of the tested phytocompounds were present in the acetone and methanol extracts of C. longa and acetone extract of A. sativum. The total phenol, flavonoid and tannins varied in the different plant extracts ranging from 0.23 to 50.56 mg GAE/g, 0.65 to 17.73 mg QE/g and 2.48 to 129.65 mg TE/g, respectively. The acetone and methanol extracts of T. violacea and A. sativum showed inhibition zones against the FOC (17–26 mm), while the water extract showed no inhibition. The minimum inhibitory concentration of the extracts ranged from 1.56 mg/mL to 50 mg/mL, with T. violacea and A. sativum showing the best activity. The methanol and acetone extracts of T. violacea and acetone extracts of A. sativum fully inhibited the mycelial growth of FOC. HPLC analysis of the extracts with the best antifungal activity revealed the presence of the following phenolic compounds: tannic acid, ascorbic acid, benzoic acid and acetyl acid in the acetone and methanol extracts of T. violacea and acetone extract of A. sativum. This research shows that T. violacea and A. sativum may be used to formulate new, safer, and ecofriendly fungicides for F. oxysporum f. sp cubense. Therefore, plant extracts could be a good alternative in managing fusarium wilt in bananas.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: FOC; Crude extracts; Qualitative preliminary screening; Quantitative analysis; Antifungal activities; HPLC; Dissertations, Academic -- South Africa.; Bananas -- Diseases and pests -- Biological control.; Fusarium wilt of banana.